2019
DOI: 10.1002/bsd2.63
|View full text |Cite
|
Sign up to set email alerts
|

The state of corporate social responsibility research in Ghana: A synthesis of literature

Abstract: There are recent calls to pay attention to the institutional requirement or the configurations of the national business system because it eventually results in the different manifestation of corporate social responsibility (CSR) in different contexts. This has led to several contestations against the suitability of transferring developed countries' CSR frameworks and ideas to developing countries. Yet literature reviews about CSR in developing countries and in Africa, in particular, are limited. This paper, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 131 publications
1
6
0
Order By: Relevance
“…Contributions to developing a community are seen here as the primary way to improve the communities in which businesses operate (Visser, 2008). Hence, our study also supports the view that CSER practices in developing countries are much related to local ideologies more than being related to formal legal and accounting regulations as the case in developed contexts (e.g., Amaeshi et al , 2006; Crinis, 2019; Damoah et al , 2019; Aboud and Diab, 2019).…”
Section: Discussionsupporting
confidence: 83%
“…Contributions to developing a community are seen here as the primary way to improve the communities in which businesses operate (Visser, 2008). Hence, our study also supports the view that CSER practices in developing countries are much related to local ideologies more than being related to formal legal and accounting regulations as the case in developed contexts (e.g., Amaeshi et al , 2006; Crinis, 2019; Damoah et al , 2019; Aboud and Diab, 2019).…”
Section: Discussionsupporting
confidence: 83%
“…The negative effect of CEO duality on CSR disclosure is in line with Giannarakis () and Sundarasen, Je‐Yen, and Rajangam (), who support the view that the effectiveness of the monitoring role of board directors is constrained by the managerial power of CEO duality by resulting in a lower transparency towards stakeholders reducing CSR reporting. This study can help us understand why a set of norms that are relatively effective in developed markets may not work in emerging markets (Damoah, Peprah, & Cobla, ; Kikwiye, ). Thus, it seems that alternative systems of corporate governance that reflect the institutional realities of these emerging markets will be needed.…”
Section: Introductionmentioning
confidence: 99%
“…The adoption of pro-environmental behavior as part of CSR activities of corporations is vital in changing the CSR narrative in Ghana to favor climate change manage-ment strategies as discovered in other jurisdictions (Raza et al, 2021). Even though synthesis of literature of CSR in Ghana from 2006 to 2018 (Damoah, Peprah, & Cobla, 2019;Amo-Mensah & Tench, 2015;Damoah et al, 2019;Ansu-Mensah et al, 2021) revealed that the philanthropic and ethical dimension of CSR are given more attention by corporations than no environmental dimension. Meanwhile, studies in Ghana have discovered negative environmental practices by corporations (Amo-Mensah & Tench, 2015;Damoah et al, 2019;Ansu-Mensah et al 2021;etc.…”
Section: Statement Of Problemmentioning
confidence: 99%
“…Even though synthesis of literature of CSR in Ghana from 2006 to 2018 (Damoah, Peprah, & Cobla, 2019;Amo-Mensah & Tench, 2015;Damoah et al, 2019;Ansu-Mensah et al, 2021) revealed that the philanthropic and ethical dimension of CSR are given more attention by corporations than no environmental dimension. Meanwhile, studies in Ghana have discovered negative environmental practices by corporations (Amo-Mensah & Tench, 2015;Damoah et al, 2019;Ansu-Mensah et al 2021;etc. ), there is little evidence on CSR perception and pro-environmental behaviors of corporate entities in Ghana.…”
Section: Statement Of Problemmentioning
confidence: 99%